Principal’s transformational and transactional leadership towards teachers’ morale at secondary school: A case study at Sekolah Menengah Kebangsaan Seri Serdang / Mu’liyanati Afzan Mohammad and Azril Abdul Manaf - Mohammad, Mu’liyanati Afzan; Abdul Manaf, Azril (Faculty of Administrative Science and Policy Studies, 2013)
This Study examined the principal transformational and transactional towards teachers’ morale in Sekolah Menengah Kebangsaan Seri Serdang. The Leadership Practices Inventory was used to collect information on the principal practices. There are 50 questionnaire were distributed to 50 respondents which are the teachers in these school. Correlation and regression tests were used to analyze the data taking into consideration the descriptive statistics. The result shows that there is a relationship between principal transformational leadership towards teachers’ morale but there is no relationship between principal transactional leadership towards teachers’ morale. The result also shows that principal transformational leadership is the most influencing leadership style towards teachers’ morale. Finally, the study recommended that school principals should imbibe a mixture of autocratic and democratic styles of leadership in their school administration in order to enhance better job performance among teachers.